Effect of lincRNA-EPS on osteoclastogenesis of RAW264.7 cells induced by RANKL and LPS: An experimental study - ZHANG Xu; WANG Yabing; SU Jiansheng (Kouqiang hemian waike zazhi)
[Objective:] To study the effect of long non-coding RNA-EPS (lincRNA-EPS) on osteoclastogenesis of RAW264.7 cells induced by receptor activator for nuclear factor-κB ligand (RANKL) and lipopolysaccharide (LPS). [Methods:] RAW264.7 cell strain overexpressing lincRNA-EPS (lincRNA-EPS OE strand) and its negative control strain were generated by transfection of lincRNA-EPS overexpressing vector and negative control vector and subsequent screening. Osteogenesis was induced with either RANKL or LPS (after pretreatment with RANKL). The cells were then stained with tartrate resistant acid phosphatase staining (TRAP staining) kit to count the number and observe the morphology of osteoclasts. Phalloidin staining was performed to detect the F-actin rings and therefore to evaluate bone-resorbing ability of osteoclasts. Real-time quantitative polymerase chain reaction (RT-qPCR) was performed to measure the mRNA levels of osteoclast-associated genes. [Results:] RAW264.7 cell strain overexpressing lincRNA-EPS and its negative control strain were generated. Neither strain showed significant difference during osteoclastogenesis (P>0.05), either induced by RANKL or LPS; for osteoclastogenesis by LPS induction, TRAP staining showed that significantly more osteoclasts were generated from lincRNA-EPS OE strain (P<0.05), while phalloidin staining showed that larger F-actin rings were generated from lincRNA-EPS OE strain, and RT-qPCR also showed that the mRNA levels of 4 osteoclastogenesis-related genes (TRAP, CTSK, DC-STAMP and ATP6v0d2) after induction were significantly lower in lincRNA-EPS OE strain (P<0.05); however, those difference were not present (P>0.05) when osteoclastogenesis was induced by RANKL. [Conclusion:] The overexpression of lincRNA-EPS inhibits LPS-induced osteoclastogenesis and the function of osteoclasts. However, the overexpression of lincRNA-EPS does not affect RANKL-induced osteoclastogenesis significantly.